The Cambridge companion to Augustine's 'Confessions' - Toom, Tarmo (Cambridge companions to religion, 2020)
"This Cambridge Companion serves as an authoritative guide to Augustine's Confessions-a literary classic and one of the most important theological/philosophical works of Late Antiquity. Bringing together new essays by leading scholars, the volume first examines the composition of the text, including its structure, genre, and intended audience. Subsequent essays explore a range of themes and concepts, such as God, creation, sin, grace, happiness, and interiority, among others. The final section of the Companion deals with its historical relevance. It provides sample essays on the reception history of the Confessions. These essays demonstrate how each generation reads the Confessions in light of current questions and circumstances, and how the text continues to remain relevant and raise new questions"